Radiation tolerance of two-dimensional material-based devices for space applications - Tobias Vogl (Nature Portfolio, 2019)
The potential of 2D materials for space applications has been surfaced recently, however a comprehensive assessment of their suitability is currently missing. Here, the authors investigate the radiation effects in Earth’s atmosphere on various devices based on 2D transition metal dichalcogenides and hexagonal boron nitride.